2019
DOI: 10.1101/754333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Musical prediction error responses similarly reduced by predictive uncertainty in musicians and non-musicians

Abstract: Auditory prediction error responses elicited by surprising sounds can be reliably recorded with musical stimuli that are more complex and realistic than those typically employed in EEG or MEG oddball paradigms. However, these responses are reduced as the predictive uncertainty of the stimuli increases. In this study, we investigate whether this effect is modulated by musical expertise. Magnetic mismatch negativity (MMNm) responses were recorded from 26 musicians and 24 non-musicians while they listened to low-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…The latency of the MMNm was significantly longer (t = 35.68, p < .001) and its amplitude was significantly larger (t = 8.37, p < .001) than those of the N1m, in the mean and peak amplitude analyses. Moreover, expertise effects were found for the MMNm (p < .001), thus reproducing in the magnetometer space the differences previously reported for combined gradiometers (Quiroga-Martinez et al, 2019a). Regarding source analyses, one-sample t-tests suggested that the main generators of both the MMNm and the N1m were located in the surroundings of primary auditory cortex, as expected (Figure 9).…”
Section: Comparison Between N1m and Mmnmsupporting
confidence: 87%
See 3 more Smart Citations
“…The latency of the MMNm was significantly longer (t = 35.68, p < .001) and its amplitude was significantly larger (t = 8.37, p < .001) than those of the N1m, in the mean and peak amplitude analyses. Moreover, expertise effects were found for the MMNm (p < .001), thus reproducing in the magnetometer space the differences previously reported for combined gradiometers (Quiroga-Martinez et al, 2019a). Regarding source analyses, one-sample t-tests suggested that the main generators of both the MMNm and the N1m were located in the surroundings of primary auditory cortex, as expected (Figure 9).…”
Section: Comparison Between N1m and Mmnmsupporting
confidence: 87%
“…The stimuli were delivered in three blocks lasting around seven minutes each and were part of a longer experimental session that included other conditions addressing questions beyond the scope of this study. Data from these conditions have been (Quiroga-Martinez et al, 2019a, 2019b and will be published elsewhere. Individual tones were created using a piano sample and had a duration of 250 ms.…”
Section: Stimulimentioning
confidence: 99%
See 2 more Smart Citations